Superalloys 718, 625, 706 and Various Derivatives (2005) 2005
DOI: 10.7449/2005/superalloys_2005_687_698
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphorus on Creep Performance of DA Alloy 718

Abstract: Achieving a balance between low cycle fatigue and creep in alloy 718 critical rotating hardware has become challenging as application conditions become more aggressive and geometries more complex. Optimization of both forge practice and of minor chemistry variations are required to meet this property balance. A review of potential factors influencing creep variation in direct age alloy 718 forgings identified phosphorus level as a statistically significant factor over the range of 50 ppm to 125 ppm. Verificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…They assumed that the decrease of creep rate was due to the solid solution strengthening of phosphorus addition. Heaney et al 11) also confirmed the beneficial effects of phosphorus on the creep properties of Inconel 718 at approximately 593°C (1 100°F), and reported that the optimum phosphorus content is in a range of 80 to 150 ppm. There are several other reports on the influence of phosphorus on the creep properties of Inconel 718, and in most cases phosphorus has a positive effect in increasing the creep rupture life.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…They assumed that the decrease of creep rate was due to the solid solution strengthening of phosphorus addition. Heaney et al 11) also confirmed the beneficial effects of phosphorus on the creep properties of Inconel 718 at approximately 593°C (1 100°F), and reported that the optimum phosphorus content is in a range of 80 to 150 ppm. There are several other reports on the influence of phosphorus on the creep properties of Inconel 718, and in most cases phosphorus has a positive effect in increasing the creep rupture life.…”
Section: Introductionsupporting
confidence: 52%
“…The results obtained in this work basically agree with those reported by Guo et al; 12) the 0.2% proof stress and tensile stress of Inconel 718 at room temperature and at 650°C did not change, and the time to rupture at 650°C, 650 MPa peaked at the phosphorus content of 0.013%. Heaney et al 11) also mentioned that controlled phosphorus addition between 80 and 150 ppm would be effective for the improvement in creep performance of Inconel 718. Although there are some differences in the chemical composition between Inconel 718 and the alloy used in this study, the suitable phosphorus content to improve creep properties is seemed to be equal.…”
Section: Creep Testmentioning
confidence: 99%
“…Other researchers consider the effect of P may come from its direct action to grain boundary [3,13]. The segregation of P to grain boundary increases the grain boundary cohesion by impeding dislocation motion, resulting in the improvement of stress rupture life.…”
Section: Discussionmentioning
confidence: 99%